From Mesenchymal Stromal Cells to Engineered Extracellular Vesicles: A New Therapeutic Paradigm - Johnson, Jancy; Shojaee, Mozhgan; Mitchell Crow, James; Khanabdali, Ramin (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSCs) are multipotent cells obtained from many tissues including bone marrow, adipose tissue, umbilical cord, amniotic fluid, and placenta. MSCs are the leading cell source for stem cell therapy due to their regenerative and immunomodulatory properties, their low risk of tumorigenesis and lack of ethical constraints. However, clinical applications of MSCs remain limited. MSC therapeutic development continues to pose challenges in terms of preparation, purity, consistency, efficiency, reproducibility, processing time and scalability. Additionally, there are issues with their poor engraftment and survival in sites of disease or damage that limit their capacity to directly replace damaged cells. A key recent development in MSC research, however, is the now widely accepted view that MSCs primarily exert therapeutic effects via paracrine factor secretion. One of the major paracrine effectors are extracellular vesicles (EVs). EVs represent a potential cell-free alternative to stem cell therapy but are also rapidly emerging as a novel therapeutic platform in their own right, particularly in the form of engineered EVs (EEVs) tailored to target a broad range of clinical indications. However, the development of EVs and EEVs for therapeutic application still faces a number of hurdles, including the establishment of a consistent, scalable cell source, and the development of robust GMP-compliant upstream and downstream manufacturing processes. In this review we will highlight the clinical challenges of MSC therapeutic development and discuss how EVs and EEVs can overcome the challenges faced in the clinical application of MSCs.